Traditional motif from the epic “ZHanysh, Bayysh” (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article presents scientific opinions about traditional motifs, which are one of the artistic means used in heroic epics, and about their artistic function, which they perform in the epic “Zhanysh, Baiysh”. Motifs such as the birth, the first exploits, and the marriage of the main characters, characteristic of heroic epics, are found in the Kyrgyz heroic epics “Manas” and are supported by convincing examples of common similarities. It is noted that traditional motifs are an artistic device used to idealize the main characters.
Keywords: motif, epic, tradition, epic work, totem, archaic plot, fiction, myth